Security of the industrial Internet of things and localization of the core technology - Guangnan NI (物联网学报)
With the industrial control system as the breakthrough point,the security problems and national network security strategy of the industrial Internet of things were analyzed in detail,and the importance of the localization of the core technology was expounded.Taking the desktop computer technology,which was one of the core technologies of the industrial Internet of things,as an example,the necessity and favorable conditions for breaking the Wintel system monopoly was expounded,two ways and key technologies to replace the Wintel system were given,and the present status and application results of the security controlled desktop computer technology system in China was analyzed.Finally,suggestions for the future development of China’s network security and information technology were put forward.